Implementation of Trait and Factor Counseling for Students Who Experience Difficulty of Choosing Language Programs - hidayat, rahmat; Daharnis, Daharnis; Iswari, Mega (Widyagogik, 2022)
This study was to determine the differences in the level of difficulty in the selection of a language majors program before and after the application of Trait and Factor counseling for class X-6 SMA NEGERI N 1 Bonjol. This research was conducted using a questionnaire, observation and interviews. Research subjects with 6 students who have difficulty choosing a language program from class X-6 SMA NEGERI 1 Bonjol, Based on the data analysis technique used is the test sign N = 5 and x = 0 obtained p = 0.031 this price is smaller than a = 0.05. Thus H0 is rejected and Ha is accepted. So the hypothesis which says "there is a significant difference between the level of difficulty in choosing a language majors program in class x-6 SMA NEGERI 1 BONJOL between the previous and after the application of counseling" Trait and Factor "can be accepted.